2021
DOI: 10.1039/d0cc06654k
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free syntheses ofN-functionalized andNH-1,2,3-triazoles: an update on recent developments

Abstract: An overview of the latest developments (2016–August 2020) in the metal-free synthesis of non-benzo-fused N-functionalized and NH-1,2,3-triazoles is provided in this feature article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 186 publications
0
35
0
1
Order By: Relevance
“…Very recently, our group reported the synthesis and spectroscopic properties of novel 1,2,3-triazole BOPAHY dyes and their corresponding triazolium salts ( Scheme 30 ) [ 84 ]. Thus, we started from N -tosyl-4,5,6,7-tetrahydroindol-4-one 118 and performed our in-house developed general metal-free triazolization reaction [ 85 , 86 , 87 , 88 , 89 ]. This route toward 1,2,3-triazoles starts from enolizable ketones, primary amines and 4-nitrophenyl azide as diazo-transfer agent.…”
Section: Synthesis Of [45]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
“…Very recently, our group reported the synthesis and spectroscopic properties of novel 1,2,3-triazole BOPAHY dyes and their corresponding triazolium salts ( Scheme 30 ) [ 84 ]. Thus, we started from N -tosyl-4,5,6,7-tetrahydroindol-4-one 118 and performed our in-house developed general metal-free triazolization reaction [ 85 , 86 , 87 , 88 , 89 ]. This route toward 1,2,3-triazoles starts from enolizable ketones, primary amines and 4-nitrophenyl azide as diazo-transfer agent.…”
Section: Synthesis Of [45]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
“…As easily accessible and highly reactive building blocks, enaminones and analogous stable enamines have been widely used in the construction of cyclic compounds, especially nitrogen-containing heterocyclic compounds. 1 Generally, depending on the substitution style of the amino group in enaminones and/or reaction conditions, the amino group in enaminones may undergo two major types of transformations: the cleavage of C–N bonds or the nucleophilic reaction of the amino group without C–N bond cleavage. Actually, both transformation modes have found broad and significant application in devising highly enriched synthetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a procedure was developed starting from FNPT 1a and primary amines that allowed for protein modification in excellent conversions without isolating the targeted aldehydes 7. Following our ongoing interest in the synthesis of 1,2,3-triazoles [36][37][38], we recognized the potential of this approach for the metal-free synthesis of 1-alkyl-4-formyl-As described by L'abbé, the equilibrium of the Cornforth rearrangement is shifted toward the triazole with the most electron-deficient substituent on the imine nitrogen. Fletcher et al, who further studied this rearrangement in 2018, observed the same trend [34].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a procedure was developed starting from FNPT 1a and primary amines that allowed for protein modification in excellent conversions without isolating the targeted aldehydes 7. Following our ongoing interest in the synthesis of 1,2,3-triazoles [36][37][38], we recognized the potential of this approach for the metal-free synthesis of 1-alkyl-4-formyl-1,2,3-triazoles 7. However, to the best of our knowledge, a metal-free and straightforward synthesis of FNPT 1a on a preparative scale was still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation